Estradiol and tamoxifen induce cell migration through GPR30 and activation of focal adhesion kinase (FAK) in endometrial cancers with low or without nuclear estrogen receptor α (ERα). - Chia-Lung Tsai; Hsien-Ming Wu; Chiao-Yun Lin; Yi-Jun Lin; Angel Chao; Tzu-Hao Wang; Swei Hsueh; Chyong-Huey Lai; Hsin-Shih Wang (PLoS ONE, 2013)
Estrogens and tamoxifen (an antiestrogen) exert their actions by activation of estrogen receptor (ER) through genomic and non-genomic mechanisms and are implicated in the development of endometrial cancer. Previous reports have demonstrated that estradiol and tamoxifen induce proliferation of human endometrial cancer cells through GPR30 (non-genomic ER) signaling pathway. Herein, we demonstrate that phosphorylation of focal adhesion kinase (FAK) is involved in cell migration induced by estradiol, tamoxifen and G1 (a GPR30 agonist) through the transmembrane ER (GPR30) in endometrial cancer cell lines with or without ERα (Ishikawa and RL95-2). Additionally, the GPR30-mediated cell migration was further abolished by administration of either specific RNA interference targeting GPR30 or an FAK inhibitor. Moreover, we have validated that the signaling between GPR30 and phosphorylated FAK is indeed mediated by the EGFR/PI3K/ERK pathway. Clinically, a significant correlation between levels of GPR30 and phophorylated FAK (pFAK) observed in human endometrial cancer tissues with low or without ERα further suggested that estrogen-induced phosphorylation of FAK and cell migration were most likely triggered by GPR30 activation. These results provided new insights for understanding the pathophysiological functions of GPR30 in human endometrial cancers.